2020
DOI: 10.3332/ecancer.2020.1101
|View full text |Cite
|
Sign up to set email alerts
|

The care of older cancer patients in the United Kingdom

Abstract: The ageing population poses new challenges globally. Cancer care for older patients is one of these challenges, and it has a significant impact on societies. In the United Kingdom (UK), as the number of older cancer patients increases, the management of this group has become part of daily practice for most oncology teams in every geographical area. Older cancer patients are at a higher risk of both under-and over-treatment. Therefore, the assessment of a patient's biological age and effective organ functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A map of the current services and projects in the UK in the field of geriatric oncology was performed by Gomes et al in 2020 [ 59 ]. It concluded that although the care of cancer patients was a significant part of daily practice, routine care of these patients did not include a formal geriatric or frailty assessment/management and the use of treatment toxicity prediction tools was not standard practice.…”
Section: Challenges and Potential Solutionsmentioning
confidence: 99%
“…A map of the current services and projects in the UK in the field of geriatric oncology was performed by Gomes et al in 2020 [ 59 ]. It concluded that although the care of cancer patients was a significant part of daily practice, routine care of these patients did not include a formal geriatric or frailty assessment/management and the use of treatment toxicity prediction tools was not standard practice.…”
Section: Challenges and Potential Solutionsmentioning
confidence: 99%
“…Inpatients will likely have more rapid trajectories of disease progression, a higher symptom burden and a poorer prognosis than patients reviewed in outpatients. Work to evaluate the potential utility in guiding treatment decisions in outpatients is ongoing (Gomes et al, 2020 ).…”
Section: Limitationsmentioning
confidence: 99%
“…A “physiological age” so derived could be factored into evidence-based cancer and treatment expectations (e.g., estimated remaining life years with cancer, without and with treatment, plus quality of life with or without treatment] to create a decisional process that is not arbitrarily distorted by age [ 68 , 69 ]. Assessing older patients with cancer in this function-based way should reduce risks of both over- and under-treatment [ 70 , 71 ].…”
Section: How Treatment Decisions Are Becoming Less Influenced By Chro...mentioning
confidence: 99%